"An Acceptable Marriage": Marriage Migration and Moral Gatekeeping in Finland. (September 2015) - Pellander, Saara
This article focuses on the role of bureaucrats in Finnish immigration administration and sheds light on how they evaluate family relations of marriage migrants. It is based on interviews with staff at the Finnish immigration office and local police stations who deal with residence permit applications on the ground of marriage. By using the analytical framework of moral gatekeeping, I identify culture, gender, and temporality as central elements of the gatekeeping procedure. The article argues that bureaucrats combine cultural relativism with an essentialist view that expects migrants to adhere to indigenous cultural norms. They expect migrants to prove a belonging to what the bureaucrats perceive of as a certain culture of origin. The article furthermore sheds light on the gendered understandings of spouses in the immigration process. Finally, it explores temporality and the awareness of how the passage of time affects migrants' marriage credentials and thereby jeopardizes bureaucrats' decision-making process.